IMPLEMENTASI KEBIJAKAN PENGELOLAAN SAMPAH DI TEMPAT PENGELOLAAN SAMPAH (TPS) BUKIT ASRI KECAMATAN GANTARANG KABUPATEN BULUKUMBA - Yusrival, Yusrival; Madani, Muhlis; Mustari, Nuryanti (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
This study purposed to find out the extent to which the successful implementation of waste management policies at TPS Bukit Asri, Polewali Village, Gantarang District, Bulukumba Regency. The research method used  qualitative which  described a problem that occurs. The data collection techniques used the method of observation, interviews, and document studies with the number of informants as many as 7 people. The results showed that the implementation of the Waste Management Policy at the Bukit Asri TPS had been  implemented well, this could be seen from 1. The behavior of organizational relations at the Bukit Asri TPS had been carried out by cooperating, committing, and coordinating with the Bulukumba Regency Spatial Planning Office. 2. The behavior of the lower implementers had also implemented waste management. This  seen from three aspects, namely organizational control, work ethic, and work professionalism of TPS managers. 3. The behavior of the target group, namely the community gave a positive response and supported the existence of waste management at the Bukit Asri TPS. Because it was considered very helpful for urban communities, especially in densely populated areas.